Education systems as contextual factors in the Technological Pedagogical Content Knowledge framework - Dobi Barišić, Karolina (Array, 2019)
Digital competences should be considered in teacher education and professional development. The Technological Pedagogical Content Knowledge (TPACK) framework represents the knowledge required by teachers in order to successfully integrate technology into the teaching process. The Survey of Pre-service Teachers’ Knowledge of Teaching and Technology (SPTKTT) is one of the inventories developed to measure the TPACK framework. The aim of this study is to validate the SPTKTT inventory in the context of the Croatian education system by the use of exploratory and confirmatory factor analysis. Results showed that the new context structure of the SPTKTT inventory consists of nine factors, while confirmatory factor analysis established that the two Content Knowledge factors can actually be unified. This can be explained by differing content organization in education systems. There were also differences in the distribution of some of the remaining factors. Internal consistency of the inventory shows high reliability.